Autonomic dysregulation in burnout and depression: evidence for the central role of exhaustion - Kanthak, Magdalena K.; Stalder, Tobias; Hill, LaBarron K.; Thayer, Julian F.; Penz, Marlene; Kirschbaum, Clemens (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'Given the important role of the autonomic nervous system (ANS) in stress regulation, astonishingly little is known about ANS functioning in burnout, a condition arising after prolonged exposure to work-related stress. The current study sought to investigate ANS modulation, as indexed by vagally-mediated heart rate variability (HRV), in relation to burnout symptomatology to (i) distinguish associations between the three dimensions of burnout [emotional exhaustion (EE), cynicism, reduced personal accomplishment] and (ii) investigate overlap in associations with depressive symptomatology. ' ' METHODS ': 'Assessments of vagally-mediated HRV (ie, root mean square of successive differences, RMSSD) were conducted in a large population-based sample from the Dresden Burnout Study [N=410, mean age 42.2, standard deviation (SD) 11.2 years; 33.4% male]. Vagally-mediated HRV was assessed for 90 seconds during an emotionally-arousing situation (venipuncture, recumbent), a 335-second recumbent recovery period, and a 335-second seated resting condition. ' ' RESULTS ': 'Results from multiple linear regression analyses revealed that EE was negatively related to RMSSD during venipuncture (=β -0.11, P=0.03) and the seated rest (β= -0.09, P=0.04) even after accounting for established ANS modulators (eg, age, body mass index). This pattern was not observed for the other dimensions of burnout. Exploratory analyses of depressive symptomatology further revealed that RMSSD was significantly and inversely associated with burnout-related symptoms but not with the core criteria of depression (eg, depressed mood). ' ' CONCLUSIONS ': 'This study presents evidence for a link between exhaustion and reduced vagal function, both in burnout and depression, suggesting that ANS modulations may not be disorder-specific but rather a psychophysiological correlate of an underlying feature shared by both conditions.
Keywords: affective disorder; autonomic dysregulation; burnout; chronic work stress; depression; dysregulation; exhaustion; heart rate variability; stress; vagal function; work stress